RESTful Java patterns and best practices : learn best practices to efficiently build scalable, reliable, and maintainable high performance RESTful services /: learn best practices to efficiently build scalable, reliable, and maintainable high performance RESTful services. (2014) - Mehta, Bhakti
No abstract available